Optimalisasi Peran Kepala Madrasah Kunci Revitalisasi Pendidikan Islam - M Royhan Kamal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic education is currently facing various challenges that require revitalization measures to improve the quality and effectiveness of the learning process. The role of the head of the madrasa becomes crucial in this revitalization process. This study aims to explore how the head of the madrasa can maximize their role in supporting the renewal and enhancement of Islamic education. The research method used is library research, which involves a review of literature on the role of the head of the madrasa and best practices in educational management. The study shows that the head of the madrasa needs to perform several key roles simultaneously. Firstly, as a leader, they must be able to motivate and inspire all members of the school to achieve the established educational goals. Secondly, in their capacity as an educator, the head of the madrasa should provide the necessary guidance and support to teachers to improve the quality of teaching and the learning process. Thirdly, as a manager, the head of the madrasa must efficiently and effectively manage school resources. Fourthly, in the role of administrator, they must ensure that school administration runs smoothly and complies with applicable regulations. Lastly, as a supervisor, the head of the madrasa needs to monitor, mentor, and improve the classroom learning process and design relevant training programs for teachers.